The impact of temporal framing on the marginal propensity to consume - Thomas Pauls (Leibniz Institute for Financial Research SAFE, 2021)
We conducted a large-scale household survey in November 2020 to study how altering the time frame of a message (temporal framing) regarding an imminent positive income shock affects consumption plans. The income shock derives from the abolishment of the German solidarity surcharge on personal income taxes, effective in January 2021. We randomize across survey participants whether their extra disposable income is presented in Euros per month, Euros per year, or Euros per ten year-period. Our main findings are as follows: In General, we find our respondents' intended Marginal Propensity to Consume (MPC) is 28.2%. Across all three treatments, the MPC is a positive function of age and being female while it is a negative function of the income increase's size, self- control, and being unemployed. Temporal framing effects are statistically and economically highly significant as we find the monthly treatment groups' average MPC 5.6 and 8.7 percentage points higher compared to the yearly and 10-yearly treatment groups. We will be able to analyze the real consumption behavior of households throughout 2021 based on re-surveying the participants as well as by using transaction-based bank data.
urn:nbn:de:hebis:30:3-582716
Keywords: E2; E6; 330; behavioral economics; saving; marginal propensity to consume; tax intervention; tax cut